Pengaruh Manajerial Kepala Sekolah dan Kompetensi Guru Terhadap Prestasi Siswa : Study Kasus Pandemic Covid-19 - Astuti, Ni Wayan Widi; Murniasih, Ni Nyoman; Putra, I Komang Agus; Mulia, Theresia; Kawamasi, Elisabet (Universitas Pendidikan Ganesha, 2022)
This study aims to determine: (1) the influence of Principal Managerial on Student Achievement, (2) the influence of Teacher Competence on Student Achievement, (3) the influence of Principal Managerial and Teacher Competencies on Student Achievement. This study uses a quantitative approach. The sample in this study amounted to 58 respondents taken from the number of teachers in SMA Negeri 2 Denpasar. Data collection techniques using observation, documentation, and questionnaires with descriptive analysis testing, testing requirements analysis and hypothesis testing and SPSS 26 The results of this study indicate that (1) the Principal Managerial variable (X1) has an effect on Student Achievement (Y) this is based on the t-count value is 3.837 which is greater than the t-table which is 2.001 with a significant value of 0.000 <0.05. (2) Teacher Competency variable (X2) has an effect on Student Achievement of Prime Card 3 (Y) this is based on the t-count value, which is 6.640, which is greater than the t-table, which is 2.001 with a significant value of 0.000 <0.05. (3) Student Achievement variable (Y) the F-count value is 26,190 which is greater than the F-table, which is 3.16. The results of the determination test show that the amount of Adjusted R Square is 0.469, which means that 46.9% of the Student Achievement variable (Y) is influenced by Principal Managerial (X1) and Teacher Competence (X2), while the remaining 53.1% is influenced by other factors. which were not included in the study.